(untitled) - Gouspillou, Noémie; Vandromme, Camille; Stefanov, Nathalie; Simon, Clémence; Elliott, Luba; Courtade, Emmanuel; Biot, Christophe; Pauze, Pierre; Spriet, Corentin (Comptes Rendus. Chimie, 2025)
In 2023, the xSublimatio project showcased a fusion of art and science, presenting an interactive platform where molecules were transformed into digital artworks within the blockchain. This innovative concept leveraged advanced artificial intelligence predictions to bridge empirical precision with creative expression, offering a unique exploration of scientific data through artistic interpretation.The creation of xSublimatio involved meticulous selection and representation of molecules, blending scientific accuracy with aesthetic appeal. Through AlphaFold-inspired insights, the project reimagined molecular design, transcending traditional boundaries.During its presentation at the GDR ChemBio conference in Strasbourg, xSublimatio sparked insightful discussions within the French chemistry community. This article explores its technical implementation, its potential for introducing blockchain and non-fungible token concepts to diverse communities, and its broader implications for interdisciplinary collaboration and decentralized science.